Cardiac risk and myocardial fibrosis assessment with cardiac magnetic resonance in patients with myotonic dystrophy - Abati, Elena; Alberti, Claudia; Tambè, Valentina; Esseridou, Anastasia; Comi, Giacomo Pietro; Corti, Stefania; Meola, Giovanni; Secchi, Francesco (Frontiers in Neurology, 2024)
IntroductionNon-invasive evaluation of myocardial tissue is a major goal of cardiac imaging. This is the case of myocardial fibrosis which is crucial in many myocardial diseases. Cardiac extracellular volume (ECV) was shown to indicate myocardial fibrosis and early cardiac involvement. With this study, our objective is to evaluate ECV measured with cardiac magnetic resonance (CMR) in patients with myotonic dystrophy type 1 (DM1) and 2 (DM2) as potential imaging biomarkers of subclinical cardiac pathology, and its relationship with demographic and clinical parameters, ECG-derived measures of cardiac conduction, and neuromuscular performance status.Materials and methodsWe retrospectively analyzed 18 DM1 patients and 4 DM2 patients without apparent cardiac disease who had CMR at our center. Differences between independent distributions were evaluated using Mann–Whitney U test, while correlations were evaluated using Spearman’s ρ.ResultsGlobal ECV in DM1 patients (median 28.36; IQR 24.81–29.77) was significantly higher (p = 0.0141) than in DM2 patients (median 22.93; IQR 21.25–24.35), and than that reported in literature in healthy subjects (p = 0.0374; median 25.60; IQR 19.90–31.90). Septal ECV was significantly higher (p = 0.0074) in DM1 (median 27.37; IQR 25.97–29.74) than in DM2 patients (median 22.46; 21.57–23.19). Global ECV showed a strong, positive correlation with septal ECV (ρ = 0.9282, p < 0.0001). We observed that DM1 women showed significantly higher global (p = 0.0012) and septal (p < 0.0001) ECV values compared to men.DiscussionWe found a significant increase in global and septal cardiac ECV in patients with DM1. These values might thus suggest that DM1 patients present an increased cardiovascular risk, mainly due to cardiac fibrosis, even in absence of overt cardiac pathology at other common cardiovascular exams. DM1 patients may also be at increased risk of early septal fibrosis, with important implications on the risk for fatal arrhythmias. In addition, our results suggest the presence of gender-related differences, with DM1 women being more prone to myocardial fibrosis. Physicians dealing with DM1 may consider CMR as a screening tool for the early identification of patients with increased cardiovascular risk.